Predicting the use of Individualized Risk Assessment for Breast Cancer - Bartle-Haring, Suzanne (2008)
PURPOSE: The purpose of this study was to investigate the decision to obtain individualized risk assessment after a breast cancer education session. METHODS: A sample of both African American and Caucasian women was used to determine if there were differences by race/ethnicity in uptake of the assessment and differences in the variables that were most predictive of uptake. The sample included 166 women between the ages of 18 and 80. Sixty-two percent of the sample were African American women. KEY FINDINGS: The results suggested that African American women and Caucasian women used different factors and used other factors differently to decide whether or not to obtain an individualized risk assessment. CONCLUSIONS AND IMPLICATIONS: These results are discussed within the context of health disparities among ethnic minority and Caucasian women with implications for breast cancer control programs. The results of this study would suggest that knowledge alone does not lead to opting for a personalized risk assessment, and that African American and Caucasian women use different pieces of information, or information differently to make decision about getting more personalized information about risk.